Модерн и творчество К. Богаевского - Айбабина, М.А. (Материалы по археологии, истории и этнографии Таврии, 2008)
Работы К.Ф. Богаевского, созданные в стилистике модерна, отличают высокий художественный уровень, творческая самостоятельность, поэтичность, высокий эстетизм. Начало творческой биографии Богаевского пришлось на годы зарождения и расцвета символизма и модерна в искусстве. Works by K. F. Bogayevsky, created in the stylistics of modernistic art, are marked by the high artistic level, creative independency, poetry and high aestheticism. The beginning of creative biography of Bogayevsky coincided with the years of spring and bloom of symbolism and modernistic style in art. Plurality of the sources of his creativity gives multifariousness of images which was introduced in this period of entrainment by the stylistics of modernistic art. In his creative work Bogayevsky gave tribute to the direction which gripped the European artistic world; however, he did not stop in his searches trying to find sources of creativity in wildlife. Bogayevsky’s resort to the stylistic of modernistic art gave a stimulus for development, for artistic search. Paintings-»tapestries», landscapes in Italian style and panels create the brightest cycle in painting by Bogayevsky, the most important series of works in creative work of the artist of the period from the beginning to the 10s of the 20th century, when he exerted himself as a real master of European scale among the painters of modernistic style.